ASSESSMENT OF STRESS OF CARE GIVERS OF PATIENTS ADMITTED IN CRITICAL CARE UNITS WITH TRAUMATIC BRAIN INJURY - N Kusuma; Shireesh S Shindhe; Nagarajaiah (Indian Journal of Psychiatric Nursing)
Traumatic brain injury (TBI) occurs when a sudden trauma causes brain damage which can result from closed head injury or a penetrating head injury, parts of the brain that can be damaged include cerebral hemispheres, cerebellum and brain stem, symptoms of TBI can be mild, moderate or severe depending on the extent of the injury to the brain, outcome can be from complete recovery to the disability or death. This study was conducted to assess the level of stress on care givers of critically ill traumatic brain injury patients hospitalized in critical care units at NIMHANS. Descriptive research design was used for the study. The data was collected from 100 caregivers selected by simple random sampling, for duration of three months. Perceived stress questionnaire (Leven Stein et al 1993) was used to collect the information. The results showed that the stress mean score was 115.46 ± 4.319. Significant association between age and marital status with stress scores showed that there was statistically significant association indicating that there was influence on stress in those variables.